The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1350/ijps.2012.14.1.262
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Aspirations among Male and Female Police Students

Abstract: A long research tradition has documented gender differences in career choices and outcomes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…When we compared women and men with similar plans for an operational career and degree of autonomous attitudes, there were no significant gender differences in attitudes towards armament. This finding is supported by previous research, which found different career plans among male and female students (Fekjaer & Halrynjo, 2012) but limited differences in the use of force (Klahm & Tillyer, 2010). Male and female students' different career plans and attitudes towards the police role explains the gender differences in attitudes towards armament, not gender differences per se.…”
Section: Resultssupporting
confidence: 85%
“…When we compared women and men with similar plans for an operational career and degree of autonomous attitudes, there were no significant gender differences in attitudes towards armament. This finding is supported by previous research, which found different career plans among male and female students (Fekjaer & Halrynjo, 2012) but limited differences in the use of force (Klahm & Tillyer, 2010). Male and female students' different career plans and attitudes towards the police role explains the gender differences in attitudes towards armament, not gender differences per se.…”
Section: Resultssupporting
confidence: 85%
“…Research finds that women perceive sex discrimination in considerations of assignments, promotions, and training opportunities (Yu, 2015). Evidence suggests that men and women value salary, opportunity, and advancement as equally important when considering careers (Bridges, 1989;Raganella & White, 2004); furthermore, males and females in law enforcement have similar promotion and advancement goals (Fekjaer & Halrynjo, 2011). Women who weigh these factors heavily in career decision-making may not believe a career in law enforcement is viable if they also believe female officers are less likely to be promoted.…”
Section: Promotion/advancement Opportunitiesmentioning
confidence: 99%
“…Women entering male dominated professions also have defied gender essentialist expectations, and a quantitative study of male and female police students in Norway indicates that the women have similar career preferences to men (Fekjaer and Halrynjo, 2012). Female police students go through a rigorous selection process.…”
Section: Gender Essentialism and Segregation Processesmentioning
confidence: 99%